Risk factors and management for early and late intrahepatic recurrence of solitary hepatocellular carcinoma after curative resection. Issue 5 (May 2015) - Cheng, Zhangjun; Yang, Pinghua; Qu, Shuping; Zhou, Jiahua; Yang, Jue; Yang, Xinwei; Xia, Yong; Li, Jun; Wang, Kui; Yan, Zhenlin; Wu, Dong; Zhang, Baohua; et al.
Abstract: Background: Intrahepatic recurrence is a significant problem for patients who have undergone a hepatic resection for hepatocellular carcinoma (HCC). The objective of the present study was to identify risk factors and evaluate the management of early and late recurrence of solitary HCC after curative resection. Methods: Included in this study were 816 patients with solitary HCC who underwent a curative partial hepatectomy. Intrahepatic recurrence in these patients was followed up retrospectively. Prognosis and therapy for the recurrence were investigated and analysed. Results: Early and late intrahepatic recurrence occurred in 423 patients and 199 patients, respectively. Multivariate analysis showed that a tumour diameter >5 cm, the absence of a tumour capsule and the presence of microvascular invasion were correlated with early recurrence, whereas cirrhosis and alphafetal protein >400 μg/l were independent risk factors contributing to late recurrence. The 5year survival of HCC patients with early recurrence was significantly lower than that of patients with late recurrence. Further curative treatment for intrahepatic recurrence offered a 5year overall survival of 56.0%, which was better than alternative management. Conclusion: Early and late recurrences of solitary HCC after curative resection are associated with different predictive factors. The time to recurrence and further curative treatment after recurrence were the best predictors of survival post recurrence.